IJTIHAD DAN URGENSINYA - Usman Jafar (Al-Risalah, 2020)
This study is intended to determine the role and urgency of ijtihad as a method of extracting and discovering Islamic law from its main sources, the Qur'an and Sunnah. This method cannot be separated from the context of the era which is always changing and developing along with the emergence of various new problems that have no legal provisions in the text.The results achieved through the ijtihad method show that Islamic law becomes elastic and develops so that it effectively becomes a solution in dealing with various problems as a result of changes and developments of the times.